O papel dos investimentos públicos em infraestrutura e o BNDES como base do financiamento: uma análise do período 1990 a 2018 - Guerra, Guilherme Fumagalli (2019)
The research embodies the fact that infrastructure investments are the main driver for economic development. The multiplier effect of these expenditures generate impacts on labor and income and enable an environment more competitive for the private sector. The research is structure to present the practical aspects beyond the financing and development of the intern infrastructure. The research present the effects of state intervention and the public expenditure on the economy over the Keynesian framework. Furthermore, it will be present the institutional model and the economic policy of infrastructure among 1990 and 2018, with emphasis to the relation between government and private sector. At last, it will be present the role of BNDES on infrastructure funding at it two phases at 1990’s and the two following decades